The Implementation Of Mubapay Electronic Transactions At Mambaul Ulum Bata-Bata Islamic Boarding School, Pamekasan, From The Perspective Of Ḥifẓ Al-Māl - Sitti Humairoh; Moh Karim (Program Studi Hukum Ekonomi Syari'ah, 2026)
This study aims to examine the implementation of the electronic transaction system Mubapay at Pondok Pesantren Mambaul Ulum Bata-Bata Pamekasan and to analyze its conformity with the Islamic principle of ḥifẓ almāl (protection of wealth). Mubapay is a digital innovation in pesantren financial management, used by students and their parents to conduct cashless transactions such as purchasing daily necessities, paying monthly fees, and transferring funds. This research employs a qualitative approach with field research as its method. Data collection techniques include observation, interviews, and documentation. The results indicate that the implementation of mubapay has been effective and well-organized. The system facilitates ease of transaction, transparent financial recording, and allows parental oversight. From the perspective of ḥifẓ al-māl, Mubapay reflects the principle of wealth protection through various aspects such as securing students’ funds from physical loss, controlling spending limits, ensuring transaction transparency, and fostering financial responsibility among students. However, challenges remain, such as limited digital literacy, dependence on network access, and the need to strengthen data security. Overall, the implementation of mubapay can be seen as a form of actualizing Islamic values in pesantren financial management oriented toward blessing and public benefit